Sustainable Tourism V 2012
DOI: 10.2495/st120191
|View full text |Cite
|
Sign up to set email alerts
|

Food and wine tourism in post-war Lebanon

Abstract: FOOD AND WINE TOURISM IN POST-WAR LEBANON LINDSAY MILICH MARCH 2011Tourism has played a major role in Lebanon since its peak period of 1930-1974; sometimes subsiding as a result of war and conflict, but always rebounding at least to some extent. Lebanon's touristic appeal includes its geographic location between the East and the West, its varied landscape (beaches and mountains), its hospitable and diverse population, and its well loved cuisine. The focus of this study was food and wine initiatives across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…In line with the above research, we found just one study of Milich (2012) on Food and Wine Tourism in Post-War Lebanon noting that while Lebanon was prone to periods of war and conflict, its tourism sector always rebounded. He found that the food and wine industry has great potential within the hospitality industry if it proceeds along sustainable and diverse pathways of development.…”
Section: Literature Reviewsupporting
confidence: 79%
See 1 more Smart Citation
“…In line with the above research, we found just one study of Milich (2012) on Food and Wine Tourism in Post-War Lebanon noting that while Lebanon was prone to periods of war and conflict, its tourism sector always rebounded. He found that the food and wine industry has great potential within the hospitality industry if it proceeds along sustainable and diverse pathways of development.…”
Section: Literature Reviewsupporting
confidence: 79%
“…In fact, traditionally, tourism in Lebanon has been oriented toward visiting religious and archeological sites along with experiencing mountains, beaches and Beirut's nightlife. While tourism is a part of Beirut's restaurant scene, the majority of customers are local residents (80%) – unlike the case for food and wine tours or tour packages that include international customers at the hotels and archeological sites (20%) (Milich, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%